Thoracic duct leakage in a patient with Type B-Non-Hodgkin lymphoma treated with transvenous retrograde access embolization: a case report - Petrini, Marcello; Colombi, Davide; Bodini, Flavio Cesare; Morelli, Nicola; Ciatti, Corrado; Quattrini, Fabrizio; Maniscalco, Pietro; Michieletti, Emanuele (Acta Biomedica Atenei Parmensis, 2023)
Thoracic duct (TD) is the largest lymphatic vessel in the body and drains the lymph at the junction between the left subclavian and jugular veins. Chylothorax (CTX) represents an accumulation of lymphatic fluid in the pleural space. We present a case of a 65 years-old man with an histologically diagnosed mediastinal type B non-Hodgkin Lymphoma, treated with chemo-immunotherapy. CT scan during follow up showed significant left side pleural effusion, amounting to 2.8 litres after drainage. Conservative treatment with low fat parenteral nutrition was started without reduction of drainage output, then lymphangiography (LP) with Lipiodol was performed demonstrating a leak in the distal TD. CTX increased in the following days, and a further LP was performed. Using transvenous retrograde access we catheterized TD at the left subclavian jugular veins using a microcatheter. The leak was treated with multiple conventional and controlled delivery microcroils and cyanoacrylate, obtaining complete embolization without residual leak.